Pengaruh Motivasi Kerja Intrinsik, Disiplin Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan KSP Koperasi Kredit Guru Kelubagolit Kabupaten Flores Timur - Ign. Soni Kurniawan; Adeodatus Primus Riantobi (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study was to determine the effect of intrinsic work motivation, work discipline and compensation on employee job satisfaction. This research uses descriptive qualitative research method. The population taken is all employees of KSP Kopdit Guru Kelubagolit, the sampling method used is non-probability sampling, and the method used is saturated sampling (census). The sample consisted of 56 respondents from KSP Kopdit Guru Kelubagolit. Methods of data collection by distributing questionnaires to respondents. The analysis of the results of this study starts with validity and reliability tests, respondent characteristics, descriptive analysis (description of research variables) and then proceeds with quantitative analysis, namely classical assumption test, linear regression analysis and hypothesis testing. The results of the Linear Regression analysis show that 1) Intrinsic Motivation X_1 has a significant effect on Job Satisfaction of the Kelubagolit Teacher Credit Cooperative Employees. 2) Work Discipline (X_2) has a significant effect on Job Satisfaction of the Kelubagolit Teacher Credit Cooperative Employees. 3) X_3 compensation has no significant effect on job satisfaction of the Kelubagolit Teacher Credit Cooperative Employees. 4) Simultaneously or together work motivation, work discipline and compensation have a significant effect on job satisfaction of the Kelubagolit Guru Credit Cooperative Employees.